MMP3 Is a Non-invasive Biomarker of Rejection in Skin-Bearing Vascularized Composite Allotransplantation: A Multicenter Validation Study - Kollar, Branislav; Uffing, Audrey; Borges, Thiago J.; Shubin, Andrey V.; Aoyama, Bruno T.; Dagot, Céline; Haug, Valentin; Kauke, Martin; Safi, Ali-Farid; Talbot, Simon G.; Morelon, Emmanuel; Dakpe, Stéphanie; et al. (Frontiers in Immunology, 2019)
Background: There is unmet need for non-invasive immunomonitoring to improve diagnosis and treatment of acute rejection in vascularized composite allotransplantation (VCA). Circulating matrix metalloproteinase 3 (MMP3) was described as a candidate non-invasive biomarker to predict treatment response to acute rejection in clinical VCA. However, larger validation studies are yet to be reported to allow for more definitive conclusions. Methods: We retrospectively measured MMP3 levels using ELISA in a total of 140 longitudinal serum samples from 6 internal and 3 external face transplant recipients, as well as 3 internal and 7 external upper extremity transplant recipients. The control groups comprised serum samples from 36 kidney transplant recipients, 14 healthy controls and 38 patients with autoimmune skin disease. A linear mixed model was used to study the effect of rejection state (pre-transplant, no-rejection, non-severe rejection and severe rejection) on MMP3 levels. Results: In VCA, MMP3 levels increased significantly (p<0.001) between pre-transplant and post-transplant no-rejection states. A further increase occurred during severe rejection (p<0.001), while there was no difference in MMP3 levels between non-severe and no-rejection episodes. A threshold of 5-fold increase from pre-transplant levels could discriminate severe from non-severe rejection with 76% sensitivity and 81% specificity (AUC=0.79, 95%CI=0.65-0.92, p<0.001). In kidney transplantation, the MMP3 levels were significantly (p<0.001) elevated during antibody-mediated rejection but not during T-cell mediated rejection (p=0.547). MMP3 levels in healthy controls and autoimmune skin disease patients were comparable with either pre-transplant or no-rejection/non-severe rejection episodes of VCA patients. Conclusion: The results of this study suggest that serum MMP3 protein is a promising marker for stratifying patients according to severity of rejection, complementary to biopsy findings.